Thin-Layer Hydroxyapatite Deposition on a Nanofiber Surface Stimulates Mesenchymal Stem Cell Proliferation and Their Differentiation into Osteoblasts. - Prosecká, Eva; Buzgo, Matej; Rampichová, Michala; Kocourek, Tomáš; Kochová, Petra; Vysloužilová, Lucie; Tvrdík, Daniel; Jelínek, Miroslav; Lukáš, David; Amler, Evžen (Journal of Biomedicine & Biotechnology, 2012)
Pulsed laser deposition was proved as a suitable method for hydroxyapatite (HA) coating of coaxial poly-e-caprolactone/polyvinylalcohol (PCL/PVA) nanofibers. The fibrous morphology of PCL/PVA nanofibers was preserved, if the nanofiber scaffold was coated with thin layers of HA (200nm and 400 nm). Increasing thickness of HA, however, resulted in a gradual loss of fibrous character. In addition, biomechanical properties were improved after HA deposition on PCL/PVA nanofibers as the value of Young's moduli of elasticity significantly increased. Clearly, thin-layer hydroxyapatite deposition on a nanofiber surface stimulated mesenchymal stem cell viability and their differentiation into osteoblasts. The optimal depth of HA was 800 nm.